Pengaruh Komunikasi, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan: PT. Brighton Bali Paradise di Denpasar Bali (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The performance of employee is one of the factors that is very influential in the work system, be it an organization. This study aims to evaluate how the performance of employee at PT. Brighton Bali Paradise in Denpasar, Bali is affected by work environment factors, communication, as well as work discipline. Primary data was employed in this study, with a total of 30 respondents comprising the study population. Sample selection was carried out utilizing the entire population. Multiple regression analysis was utilized as the data analysis method. Data processing was conducted utilizing the SPSS Windows software program. From the results of the test analysis, partial positive as well as substantial impact between communication partially on employee performance, partial positive as well as substantial impact between work discipline on performance of employee, positive, also insubstantial between partial work environment on performance of employee and communication (X1), work discipline (X2) as well as work environment (X3), on the performance of employee simultaneously also significantly influence employee performance. Hopefully, that management can pay attention to employees so that they can communicate well, schedule meetings or build teams. Organizing seminars that can remind employees to improve work discipline, carry out evaluations related to the work environment more frequently